Weighted K-Nearest Neighbor Classification Algorithm Based on Genetic Algorithm - Xuesong Yan (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
K-Nearest Neighbor (KNN) is one of the most popular algorithms for data classification. Many researchers have found that the KNN algorithm accomplishes very good performance in their experiments on different datasets. The traditional KNN text classification algorithm has limitations: calculation complexity, the performance is solely dependent on the training set, and so on. To overcome these limitations, an improved version of KNN is proposed in this paper, we use genetic algorithm combined with weighted KNN to improve its classification performance. and the experiment results shown that our proposed algorithm outperforms the KNN with greater accuracy. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.2534